2023
DOI: 10.2196/44741
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Diseases and Sociodemographic Characteristics Associated With Online Health Information Seeking and Using Social Networking Sites: Nationally Representative Cross-sectional Survey in Japan

Abstract: Background In an aging society, worsening chronic diseases increase the burden on patients and the health care system. Using online health information including health information via social networking sites (SNSs), such as Facebook and YouTube, may play an important role in the self-management of chronic diseases and health promotion for internet users. Objective This study aims to improve strategies for promoting access to reliable information for the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Studies have shown that being female and having a higher educational background are the strongest correlates of seeking health information from web-based sources [ 12 , 22 , 29 , 53 , 54 ]. Similar associations have also been suggested with regard to offline health information seeking [ 22 , 29 , 54 ], except for null or inverse associations between education and television exposure [ 38 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have shown that being female and having a higher educational background are the strongest correlates of seeking health information from web-based sources [ 12 , 22 , 29 , 53 , 54 ]. Similar associations have also been suggested with regard to offline health information seeking [ 22 , 29 , 54 ], except for null or inverse associations between education and television exposure [ 38 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar associations have also been suggested with regard to offline health information seeking [ 22 , 29 , 54 ], except for null or inverse associations between education and television exposure [ 38 , 75 , 76 ]. Studies also suggest that younger age is associated with web-based health information seeking [ 12 , 22 , 53 ], whereas older age is associated with offline health information seeking [ 22 , 28 ]. Our findings are generally consistent with these previous findings, except for findings regarding the role of sex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3] Therefore, it is of great significance to achieve effective management of elderly individuals with chronic diseases. [4] YY and SW contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%